Opioid Use Disorder Treatments: An Evidence Map. (1st December 2022) - Sugarman, Allison; Vittitow, Alexandria; Cheng, Anna; Malone, Mia; McDonald, Ryan; Pace, Nancy; Williams, Ololade; Tofighi, Babak; McNeely, Jennifer; Schatz, Daniel; Roberts, Timothy; Hey, Spencer Phillips; et al.
Abstract: Background: Evidence maps are emerging data visualization of a systematic review. There are no published evidence maps summarizing opioid use disorder (OUD) interventions. Aim: Our aim was to publish an interactive summary of all peer-reviewed interventional and observational trials assessing the treatment of OUD and common clinical outcomes. Methods: PubMed, Embase, PsycInfo, Cochrane Central Register of Clinical Trials, and Web of Science were queried using multiple OUD-related MESH terms, without date limitations, for English-language publications. Inclusions were human subjects, treatment of OUD, OUD patient or community-level outcomes, and systematic reviews of OUD interventions. Exclusions were laboratory studies, reviews, and case reports. Two reviewers independently scanned abstracts for inclusion before coding eligible full-text articles by pre-specified filters: research design, study population, study setting, intervention, outcomes, sample size, study duration, geographical region, and funding sources. Results: The OUD Evidence Map (https://med.nyu.edu/research/lee-lab/research/opioid-use-disorder-treatment-evidence-map) identified and assessed 12, 933 relevant abstracts through 2020. We excluded 9455 abstracts and full text reviewed 2839 manuscripts; 888 were excluded, 1591 were included in the final evidence map. The most studied OUD interventions were methadone (n = 754 studies), buprenorphine (n = 499), and naltrexone (n = 134). The most common outcomes were heroin/opioid use (n = 708), treatment retention (n = 557), and non-opioid drug use (n = 368). Clear gaps included a wider array of opioid agonists for treatment, digital behavioral interventions, studies of OUD treatments in criminal justice settings, and overdose as a clinical outcome. Conclusion: This OUD Evidence Map highlights the importance of pharmacologic interventions for OUD and reductions in opioid use. Future iterations will update results annually and scan policy-level interventions. Highlights: This opioid use disorder (OUD) evidence map allows researchers and clinicians to rapidly survey the entirety of the OUD literature through a publicly available digital resource. The most well-studied OUD interventions to date are methadone, buprenorphine, and naltrexone medication treatments. Evidence gaps include opioid agonist therapies other than buprenorphine and methadonesuch as hydromorphone.